'Who is in crisis? With reference to the debates about the 'crisis of masculinity', discuss about poverty, unemployment, or other social issues, and its effects on women'. But Whose crisis is it after all? - Schranz, Edit (METSZETEK Társadalomtudományi Folyóirat, 2022)
-